Avaliação do comportamento da mecânica respiratória e dos testes de exercício cardiopulmonar no pré e pós-operatório de pacientes submetidos à toracotomia para tratamento de doenças malignas e benignas, sua relação com as complicações pós-operatórias e com a qualidade de vida - Arruda, Karine Aparecida [UNESP] (2016)
Introduction: Thoracic surgeries are performed routinely for treatment of cardiopulmonary diseases and sometimes for diagnostic purposes, generating postoperative repercussions in lung volumes and pulmonary capacity. Despite advances in surgical techniques and pre, intra and postoperative care, some patients have postoperative complications (POC), resulting in patients and health systems impairment. Thus, inexpensive tests has been investigated in the preoperative evaluation. Additionally, postoperative cardiopulmonary recovery is not fully acknowledged and also, there seems to be a discrepancy between the predicted recovery and the observed postoperatively. At the same time, the quality of life has not been entirely studied and correlated to risk predictors tests. Objective: To determine whether cardiopulmonary exercise testing, pulmonary function and respiratory muscle strength and risk indexes are able to differentiate patients who have higher chances of developing POC; describe the evolution of the effects of thoracotomy in cardiopulmonary function, from the first day until the third month of the postoperative period; assess whether the quality of life correlates to functional values found pre-and postoperatively. Method: Patients elected for thoracotomy were evaluated from February 2010 to December 2014. Spirometry, manometry, six-minute walk test (6MWT), stair climbing test (SCT), were performed and the quality of life questionnaire SF 36 was applied. POC were recorded from the immediate postoperative period until hospital discharge. Patients were classified in two groups, according to the absence (A) or presence (B) of POC and assessed from the first day after surgery until the hospital discharge and when returned to the ambulatory, two and three months postoperatively (1M, 2M and 3M). Patients were then analyzed in two subgroups; one composed by patients that have lung cancer and the other for those who had undergone major surgeries (pneumonectomy, lobectomy and bilobectomy), both comparing those with or without POC. Results: A prospective cohort study evaluating POC as outcome. We evaluated 97 patients, 12 (13%) had POC. The age, length of surgery, anesthesia and drainage, as the postoperative hospital and ICU length of stay were higher in group B (p <0.05). About respiratory tests, forced vital capacity (FVC), forced expiratory volume in first second (FEV1) and peak flow (PEF) were significantly lower in patients with POC. Patients who had complications traveled a shorter distance (Group A: 562.63 ± 88.64; Group B: 476.13 ± 60.79; p = 0.0010) and took longer to complete the SCT (Group: 44 75 ± 16.45; Group B: 63.58 ± 23.16, p = 0.0007 *). 6MWD demonstrate a protective factor for this group after multivariate regression. Cutoffs were determined by the ROC curve for FEV1 (1.7 L), 6MWT (537 m) and SCT (47.5 sec). Further regression based on that cutoff demonstrated that 6MWT SCT and extent of surgical procedure had associations with POC. Respiratory muscle strength values were similar to the preoperative period, in Group A, as well as 6MWT at 1M postoperative follow-up. After 2M FVC, FEV1 (L) and time in SCT returned to PRE values in group A. Related to Quality of life, the capacity, physical aspects, A dimension and total score showed differences between moments, but mental health, physical function, general health, B dimension and total score showed correlation to 6MWT distance and SCT time. Conclusion: The distance in 6MWT, the time in the SCT and the extent of the surgical procedure were able to predict surgical risk in patients undergoing thoracotomy. In the third month after surgery, regardless of the presence or absence of CPO, all variables for specific respiratory and cardiopulmonary evaluation returned to values similar to initial and also the quality of life appears to correlate with performance from exercise tests in patients that underwent thoracotomy.